The Council of Nicaea on baptism - van de Beek, Abraham (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
The canons of the Council of Nicaea mention baptism three times: solid education into baptism is required, baptism by heretics is refuted, and baptism by schismatics is accepted. This article deals with the background of these decisions in the theology of that time, with special attention to the differences between Rome and the rest of Christianity. The Western tradition culminated in Augustine’s theology on baptism, which dates from the Roman practice of the third century up to the Council of Nicaea.